2019
DOI: 10.1186/s13019-019-0944-5
|View full text |Cite
|
Sign up to set email alerts
|

LVAD with concomitant rapid deployment valve implantation – a case report

Abstract: Background Aortic valve insufficiency can have significant hemodynamic consequences for patients with left ventricular assist devices. A circulation loop can limit systemic blood flow and increase left ventricular filling pressure. Case presentation A 64-year-old male with non-ischemic dilated cardiomyopathy underwent Heartware™ HVAD left ventricular assist device implantation with successful concomitant aortic valve replacement with an Edwards Intuity rapid deployment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Rapid deployment (RD)-AVR and TAVR have a shorter cross-clamping time and an overall procedural time, which minimizes the risk of intraoperative myocardial ischemia ( 5 , 14 , 15 ). Rahmanian et al examined 163 patients undergoing RD-AVR and reported the mean cross-clamping and cardiopulmonary times as 55 ± 23 and 88 ± 38 min respectively, which were relatively lesser than those of the control group (77 ± 22 and 105 ± 38 min), respectively, whereas in-hospital mortality rates of both the RD-AVR and control groups were similar [1.8%, ( n = 3/163); p = 1.000] ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid deployment (RD)-AVR and TAVR have a shorter cross-clamping time and an overall procedural time, which minimizes the risk of intraoperative myocardial ischemia ( 5 , 14 , 15 ). Rahmanian et al examined 163 patients undergoing RD-AVR and reported the mean cross-clamping and cardiopulmonary times as 55 ± 23 and 88 ± 38 min respectively, which were relatively lesser than those of the control group (77 ± 22 and 105 ± 38 min), respectively, whereas in-hospital mortality rates of both the RD-AVR and control groups were similar [1.8%, ( n = 3/163); p = 1.000] ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their key findings were as follows: (i) reduced cross-clamping (73.8 ± 37.5 and 107 ± 14.9 min) and procedural times (3.4 ± 1.0 and 3.7 ± 0.5 h); (ii) higher rates of new permanent pacemaker implantation leading to longer hospital stay in the RD-AVR group (∼7%); and (iii) similar rates of early myocardial infarction, stroke, and early mortality in both groups ( 17 ). Holloway et al performed RD-AVR using a 23-mm Edwards INTUITY valve (Edwards Lifesciences, Irvine, CA, United States) in an AI patient undergoing concomitant LVAD implantation ( 14 ). In the case-series reported by Gangahanamaiah and Marasco ( 18 ), RD-AVR was performed using the Perceval valve (LivaNova, London, United Kingdom).…”
Section: Discussionmentioning
confidence: 99%